2019
DOI: 10.1111/papr.12816
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution in Low Back Pain: A Prospective Genetic Association Study

Abstract: Objectives Chronic pain is one of the most common reasons individuals seek medical attention. It is a major issue because of the wide interindividual variability in the analgesic response. This might be partly explained by the presence of variants in genes encoding molecules involved in pharmacodynamics and pharmacokinetics. The aim was to analyze opioid effectiveness in chronic low back pain (CLBP) relief after opioid titration, unveiling the impact of pharmacogenetics. Methods The study included 231 opioid‐n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…Elens et al [22] investigated the association of rs6517442 and opioid requirements (morphine or remifentanil) in 34 preterm infants requiring endotracheal intubation, reporting that those with the AA genotype needed more time to reach a pain-free state after intubation than infants with the AG or GG genotypes. This nding was consistent with Margarit et al [20] and Nishizawa et al [10] (Table 2), who also investigated rs6517442 and reported similar associations for carriers of the A allele and pain intensity [20], or requirement for rescue analgesia [10]. The study by Matic et al [12], however, reported no associations for rs6517442.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Elens et al [22] investigated the association of rs6517442 and opioid requirements (morphine or remifentanil) in 34 preterm infants requiring endotracheal intubation, reporting that those with the AA genotype needed more time to reach a pain-free state after intubation than infants with the AG or GG genotypes. This nding was consistent with Margarit et al [20] and Nishizawa et al [10] (Table 2), who also investigated rs6517442 and reported similar associations for carriers of the A allele and pain intensity [20], or requirement for rescue analgesia [10]. The study by Matic et al [12], however, reported no associations for rs6517442.…”
Section: Discussionsupporting
confidence: 88%
“…Two studies have been conducted in patients with advanced cancer, and consistent with our ndings, both have reported no association for rs2070995 and opioid response [12,13]. Mixed results were seen for studies in postoperative pain [5,10], and associations were shown for two studies in chronic pain, reporting carriers of the A allele to be associated with a signi cantly higher pain intensity [20] and higher opioid requirements [11].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“… Study reference Therapeutic area Study site, design and included participants Intervention Case numbers and MAF* Study findings Matic et al 12 Advanced cancer 238 advanced cancer patients referred to a pain consultation service due to inadequate analgesia, Netherlands Opioids (fentanyl 73.3%, oxycodone 43%, hydromorphone 11%, morphine 5%, buprenorphine 5%) with 9% requiring ketamine as an adjuvant analgesic GG (n = 10) GA (n = 81) AA (n = 147) No association was found between genotypes and morphine equivalent dose (MED) or relative change in MED from baseline. No association was found for use of ketamine as an adjuvant analgesic Oosten et al 13 Advanced cancer 335 moderate-to-severe cancer-related pain, Netherlands Opioids (oxycodone, morphine, fentanyl, hydromorphone) GG (n = 215) GA + AA (n = 120) No association between genotypes and opioid failure, defined as rotation to another opioid or treatment with intrathecal opioids due to insufficient pain control and/or side effects, or the use of palliative sedation because of refractory symptoms associated with opioid treatment in the dying phase Lotsch et al 11 Chronic pain 352 chronic pain patients treated for pain of various reasons in tertiary outpatient care, Germany Opioids (morphine, fentanyl, buprenorphine, oxycodone, tilidine, tramadol, hydromorphone, dihydrocodeine, levomethadone, piritramide) AA (n = 17) MAF = 0.2 AA genotype associated with a significantly higher oral MED than combined AG and GG genotypes, with no significant difference in AA genotype distribution for pain diagnoses or opioid used, and no significant difference in pain score Margarit et al 20 Chronic pain 222 patients with chronic lower back pain referred for opioid prescription, Spain Opioids (fentanyl, tramadol, oxycodone, morphine, tapentadol, buprenorphine) AA (n = 63) AG (n = 33) GG (= 5) MAF = 0.21 Carriers of the A allele (AA and AG) were associated with a significantly higher pain intensity at the final visit and at the follow up visit (2–4 years later) than the GG genotype Bruehl et al …”
Section: Resultsmentioning
confidence: 99%
“…A study with 231 opioid-naïve patients revealed that those with the COMT G472A-AA genotype (rs4680) and KCNJ6 A1032G-A allele (rs2070995) required higher dosing. When a higher pain intensity was present, they responded differently to opioid titration with higher pain intensity, thereby requiring higher dosing [106] The single-nucleotide polymorphisms in genes closely related to pain transmission and the metabolism of opioids may cause patients with cLBP to possibly be predisposed to excessive sensitivity and variation in the effects of opioid analgesics.…”
Section: Pharmacogenomics In Management Of Clbpmentioning
confidence: 99%